Computational Methods in Molecular Imaging Technologies - Gunjan, Vinit Kumar; Shaik, Fahimuddin; Venkatesh, C.; Amarnath, M.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2017)
This book highlights the experimental investigations that have been carried out on magnetic resonance imaging and computed tomography (MRI & CT) images using state-of-the-art Computational Image processing techniques, and tabulates the statistical values wherever necessary. In a very simple and straightforward way, it explains how image processing methods are used to improve the quality of medical images and facilitate analysis. It offers a valuable resource for researchers, engineers, medical doctors and bioinformatics experts alike.
1.Introduction -- 2.Artifacts Correction in MRI Images -- 3.Spiral Cone-beam CT Reconstruction -- 4.Visual Quality Improvement of CT Image Reconstruction with Quantitative Measures -- 5.References.
Keywords: Biomedical engineering; Signal processing; Radiology; Image processing -- Digital techniques; Computer vision; Medical informatics; Bioinformatics; Biomedical Engineering and Bioengineering; Signal, Speech and Image Processing; Radiology; Computer Imaging, Vision, Pattern Recognition and Graphics; Health Informatics; Computational and Systems Biology